Effect of aeration on growth and production of fish in intensive aquaculture system in earthen ponds (Journal of the Bangladesh Agricultural University, 2017)
An experiment was conducted to assess the effect of aeration using blower on growth and production of tilapia (Oreochromis niloticus) in intensive aquaculture system in six (6) earthen ponds at BAU campus, Mymensingh from May to September, 2016. Treatment 1 (T1) with 3 aerated ponds and Treatment 2 (T2) with 3 non-aerated ponds were designed with similar stocking density (300/decimal) of tilapia. Oxygen supply was ensured by blower for 9 hours daily when oxygen depletion occurs in pond water. Fish growth, pond water and soil quality parameters were sampled and assessed. The DO content in the aerated ponds was higher (7.23 mg/l) from the beginning to the end of experiment compared to non-aerated ponds (2.33 mg/l). There were significant differences (p